Aerobic and anaerobic organism productivity as factors that determine the level of physical health - Serorez, T.B.; Navka, P.I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to identify and assess the level of physical health of men of the first coming of age 21-23 years. Material : the study involved 413 students and 17 teachers and sports doctors. Results : the influence of cross-country training aerobic and anaerobic focus on physical performance, aerobic and anaerobic performance of the student body. The efficiency impact exercises using running loads of aerobic and anaerobic focus on the physical health of students. It is proved that the level of aerobic performance drops to safe limits and requires correction. To correct the body's aerobic performance is recommended to use for running load. Conclusions: found that the correction would be the most efficient and effective through the development and implementation of health technologies based on the use of extracurricular classes jogging exercises. It should take into account the frequency and methods of learning, physical work mode power supply and energy value of each class.